2(x+1)-3(x-2)=-x+6

Simple and best practice solution for 2(x+1)-3(x-2)=-x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+1)-3(x-2)=-x+6 equation:


Simplifying
2(x + 1) + -3(x + -2) = -1x + 6

Reorder the terms:
2(1 + x) + -3(x + -2) = -1x + 6
(1 * 2 + x * 2) + -3(x + -2) = -1x + 6
(2 + 2x) + -3(x + -2) = -1x + 6

Reorder the terms:
2 + 2x + -3(-2 + x) = -1x + 6
2 + 2x + (-2 * -3 + x * -3) = -1x + 6
2 + 2x + (6 + -3x) = -1x + 6

Reorder the terms:
2 + 6 + 2x + -3x = -1x + 6

Combine like terms: 2 + 6 = 8
8 + 2x + -3x = -1x + 6

Combine like terms: 2x + -3x = -1x
8 + -1x = -1x + 6

Reorder the terms:
8 + -1x = 6 + -1x

Add 'x' to each side of the equation.
8 + -1x + x = 6 + -1x + x

Combine like terms: -1x + x = 0
8 + 0 = 6 + -1x + x
8 = 6 + -1x + x

Combine like terms: -1x + x = 0
8 = 6 + 0
8 = 6

Solving
8 = 6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| x^3-11x=-28 | | 2(2x+5)=6(x+1) | | ln(1.47)= | | 11-5x=31x+19 | | 5-2(3+x)=9(x-4) | | 16-6*2= | | a*3+5=10 | | 4x^3-12x^2-5=0 | | x^4+1.092=0 | | (5ab-b)+(7ab-12b)= | | 2abs(x-1)=abs(3x-4) | | (6xy+7x)(2x+5y)= | | -3+9-4= | | x-.13x=107000000 | | x+.13x=107000000 | | 4x^3+15x^4-4x=0 | | 2x^3-3x^2-12x+8=0 | | 8(x-0.5)-(3x-2)=5*1.3-1.5(11-6X) | | 2(5-6d)=7(d+9) | | 4(5a-3)=12 | | y-6x=24 | | x+(x+19)=89 | | 0.2(3x+3)=6(8x-3) | | 8x+56=0 | | 7-2a=-28+8a | | 10-2(2.5-13.5x)-6x=140-(11x+7) | | 7a+4=28-a | | 5464=656*296 | | -5a-7=28 | | 11-5y=2+y | | 7-a=-28+3a | | -3+2y=3-y |

Equations solver categories